2022
DOI: 10.3390/machines10080648
|View full text |Cite
|
Sign up to set email alerts
|

Tracked Locomotion Systems for Ground Mobile Robots: A Review

Abstract: The paper discusses the state-of-the-art of locomotion systems for ground mobile robots comprising tracks. Tracked locomotion, due to the large contact surface with the ground, is particularly suitable for tackling soft, yielding, and irregular terrains, but is characterized by lower speed and energy efficiency than wheeled locomotion, and lower obstacle-climbing capability than legged locomotion. Therefore, in recent years academic and industrial researchers have designed a wide variety of hybrid solutions, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 69 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…These robots are long and thin and have the advantages of tracked locomotion. Tracked robots [17] are particularly suitable for uneven and yielding grounds, thanks to their large contact surface with the terrain. On the other hand, their speed and efficiency are lower with respect to wheeled ones.…”
Section: Introductionmentioning
confidence: 99%
“…These robots are long and thin and have the advantages of tracked locomotion. Tracked robots [17] are particularly suitable for uneven and yielding grounds, thanks to their large contact surface with the terrain. On the other hand, their speed and efficiency are lower with respect to wheeled ones.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion between leg and track locomotion to increase mobility in unstructured environments and soft terrains is an interesting point 15 . Leg track hybrid is fairly popular for difficult environments, provided that speed and energy efficiency are not crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Tracked robots working in rugged environments such as urban ruins or outdoor woodlands often use controllable flippers—also known as sub‐tracks—to promote their traversal capabilities (Bruzzone et al, 2022), as shown in Figure 1. However, these flippers require extra control efforts, making the articulated tracked robots harder to control compared with the ordinary ones.…”
Section: Introductionmentioning
confidence: 99%